Knowledge, Attitudes, and Practices Related to Leptospirosis among Urban Slum Residents in Brazil - Navegantes de Araújo, Wildo (The American Society of Tropical Medicine and Hygiene, 2013)
Leptospirosis disproportionately affects residents of urban slums. To understand the knowledge, attitudes, and practices regarding leptospirosis, we conducted a cross-sectional study among residents of an urban slum community in Salvador, Brazil. Of the 257 residents who were interviewed, 225 (90%) were aware of leptospirosis and more than two-thirds of respondents correctly identified the modes of disease transmission and ways to reduce exposure. However, study participants who performed risk activities such as cleaning open sewers had limited access to protective clothing such as boots (33%) or gloves (35%). Almost all respondents performed at least one activity to prevent household rat infestation, which often included use of an illegal poison. Our findings support the need for interventions targeted at the individual and household levels to reduce risk of leptospirosis until large-scale structural interventions are available to residents of urban slum communities.